Analisis Fungsi Narasi Model Vladimir Propp dalam Film Surat dari Praha - Deden Mauli Darajat; Muhammad Badruzzaman (Fakultas Ilmu Komunikasi Universitas Pancasila, 2020)
This study aims to determine the struggle of a young woman to hand over a mailbox and get the signature of an old man in Prague. The scene is visualized in the film Surat from Prague. Then this study also sought the meaning of the struggle contained in each scene in the film. The approach used in this study is qualitative with a narrative analysis method that uses the character of the Vladimir Propp performer's function. The focus of this research is to describe the description of 31 character functions, knowing the opposing opposition characters in the film. The data collection technique used by the writer is watching the original film Surat from Prague and conducting interviews with the film's writer, M. Irfan Ramli. The results obtained from this study are the function of actors as many as 16 functions of the meaning of the struggle of 31 functions of the perpetrators. Starting with the initial situation which is then followed by the function of the perpetrator. There is a repetition of functions that occur but in different events. As in narration 4 and 8 both have the Mediation function. The structure of the function of the meaning of the struggle in the film Letter from Prague when arranged as follows: α, M, ↑, B, A, Rs, γ, B, D, ε, ε, E, C, N, H, and Ex.